2005
DOI: 10.1158/1078-0432.ccr-04-1859
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Expression in Stromal Cells of Endometrioid Endometrial Cancer Correlates with Poor Survival

Abstract: Purpose and Experimental Design: To assess the prognostic significance of intratumoral aromatase in endometrioid endometrial cancer, sections from 55 patients with endometrial cancer were evaluated for expression of aromatase using immunohistochemistry, and the correlation between aromatase expression and clinicopathologic parameters were analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 37 publications
2
42
1
Order By: Relevance
“…Immunohistochemical studies of the biosynthesis and metabolism of estrogen in EC confirm that estrogen-metabolizing enzymes, such as 17b-HSD types 2 and 5, are present in the cytoplasm of tumor cells but not stromal cells (Ito et al 2006). By contrast, aromatase is more highly expressed in stromal than tumor cells (Watanabe et al 1995, Sasano et al 1996, and its expression is correlated with poor survival (Segawa et al 2005). To date, there has been no direct confirmation of stromal-tumor interactions mediated by estrogen signaling and the transactivation of ERE by endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical studies of the biosynthesis and metabolism of estrogen in EC confirm that estrogen-metabolizing enzymes, such as 17b-HSD types 2 and 5, are present in the cytoplasm of tumor cells but not stromal cells (Ito et al 2006). By contrast, aromatase is more highly expressed in stromal than tumor cells (Watanabe et al 1995, Sasano et al 1996, and its expression is correlated with poor survival (Segawa et al 2005). To date, there has been no direct confirmation of stromal-tumor interactions mediated by estrogen signaling and the transactivation of ERE by endometrial stromal cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA and protein of aromatase are detectable in EC but are absent in disease-free endometrium (Bulun et al 1994, Watanabe et al 1995. Furthermore, the endometrial cancer patients with aromatase-positive stromal cells have poor survival prognosis compared with patients with aromatase-negative stromal cells (Segawa et al 2005). This evidence also suggests that aromatase is a key enzyme in the etiology of EC; however, the participation of local estrogen in the activation of ER in individual EC tumor cells has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatase expression was significant, both at the protein and mRNA levels, at the site of frank invasion in endometrial carcinoma, suggesting induction of aromatase expression by tumor-stromal interactions. Recently, Segawa et al reported a significant correlation between aromatase immunoreactivity in stromal cells and poor prognosis in 55 patients with endometrial carcinoma [21]. This positive linkage indicates that local aromatase expression plays a role in tumor progression through the formation of in situ estrogens.…”
Section: ) Aromatasementioning
confidence: 97%
“…Aromatase is a key enzyme in the synthesis of estrogens and its levels in breast carcinoma tissues have been found to be significantly higher than those in benign breast lesions [5]. Expression of aromatase has also been detected in human endometrial carcinoma [20,21]. Our laboratories previously reported marked aromatase immunoreactivity and mRNA, mainly in the stromal cells or fibroblasts of endometrioid endometrial carcinoma, but not in normal or hyperplastic endometrium [20] (Fig.…”
Section: ) Aromatasementioning
confidence: 99%
“…In addition, a significant correlation was detected between aromatase expression in stromal cells and poor prognosis in the patients with endometrial carcinoma (Segawa et al 2005), although several studies reported that aromatase expression was demonstrated in carcinoma and stromal cells together (Segawa et al 2005, Jongen et al 2009, Che et al 2014. It is very important to consider in vitro stromal-carcinoma cell interactions when studying aromatase expression in vitro.…”
Section: :7mentioning
confidence: 99%